Neo-Slave Narrative: Depiction of Enslavement in Whitehead’s "The Underground Railroad" - Syahrul Baihaqi (Morphosis: Journal of Literature, 2024)
This study discusses the portrait of slavery in neo-slave narrative in the novel The Underground Railroad by using contextual based interpretation methodology and applying Ashraf Rushdy’s theory of neo-slave narratives. In writing this research, the author analyzes the form of ill-treatment by white American towards black African-American as slaves. Not only that, the author also discusses slaves’ struggle in their quest of freedom to escape from slavery institution. At the end of the analysis, it was found out that Whitehead’s novel contains form of violence and discrimination towards slaves and also the journey of protagonist character in striving for her freedom. Keywords: neo-slave narrative, racism, slavery.